Petrophysical measurements of sandstone samples extracted from an outcrop - Peleg Haruzi; Regina Katsman; Matthias Halisch; Nicolas D Waldmann; Baruch Spiro (PANGAEA, 2019)
Petrophysical measurements of samples extracted from 3 consecutive sandstone layers from an outcrop, in lower Cretaceous sandstone from North of Israel. The data includes: Grain size distribution, mercury intrusion porosimetry, XRD, porosity and permeability, micro-CT images. Further description in read_me file.
Supplement to: Haruzi, P et al. (2021): Benchmark study using a multi-scale, multi-methodological approach for the petrophysical characterization of reservoir sandstones. Solid Earth, 12(3), 665-689, https://doi.org/10.5194/se-12-665-2021